Concept Hifz An-Nasl in Ticak Kacang Marriage, Dayak Siang Traditional - Akhmad Kamil Rizani; Baitul Dawiyah (Al Qalam, 2023)
This study discusses the traditions of the Dayak Siang community in Murung Raya Regency, Central Kalimantan, namely the Ticak Kacang traditional marriage, in which the bride and groom are married on a gong covered with mats made of peanut leaves. Men and women who love each other or are considered ready to marry are immediately united in marriage to avoid unwanted things, such as having children out of wedlock. Ticak Kacang marriage is still maintained today as a local cultural marriage. Another reason this traditional marriage is still being carried out is as an alternative for couples who conflict with the formal rules that apply, such as the age of marriage. This research was conducted using qualitative methods with data collection using the documentation method. The results of this study are that the Ticak Kacang traditional marriage is a way for the community to maintain the sanctity of the village, avoid behaviour that is not in accordance with prevailing customary norms, and demonstrate the simple life they practice. Second, Muslims who carry out the Ticak Kacang wedding tradition continue to carry out Islamic wedding processions so that they are legally religious and state law and can preserve customary law traditions.